Cultivation strategies in irrigated rice area for red rice control: Case study - Vicente, Sheilise Pedroso; Cunha, Vinícius dos Santos; Conceição, Chaiane Guerra da; Fontanela, Eracilda; Jaques, Lanes Beatriz Acosta; Fipke, Glauber Monçon; Ferreira, Alessandra Machado; Segabinazzi, Eliza Micaela; Passos, Talisson Garcia; Moraes, Stefani Refatti (Seven Editora, 2023)
Red rice (Oriza sativa L.) It is the most important weed for rice cultivation, and can reduce productivity. With the advent of the Clearfield® system, it became possible to control it using herbicides, belonging to the chemical group of imidazolinones. However, several cases of red rice resistant to these herbicides have already been identified, intensifying the problem especially when rice is sown in dry soil. The objective of this work was to describe the potential of different cropping systems in rice areas to reduce the presence of red rice resistant to these herbicides, through a case study conducted in a field. The work was conducted in the municipality of Manoel Viana, located on the Western Border of Rio Grande do Sul, during the 2021/2022 agricultural year, using 3 treatments: minimum crop (CM) and pre-germinated (PG). This commercial crop had been implanted under the minimum tillage system for several years before the implementation of the treatments. The presence of susceptible and resistant red rice was evaluated in soil samples collected after the 2021/2022 harvest. The samples were then stratified at the following depths: 0.0-0.15m and 0.15-0.30m. At the same soil collection points, in each field, rice was harvested to estimate grain yield (kgha-1), grain mass and whole grain yield. A higher number of red rice seeds was observed in the area cultivated in the pre-germinated system, but only 7.95% of these seeds generated plants in the previous harvest. However, in minimum cultivation, 33.86% of the seeds generated plants. This result, combined with the higher average yield and percentage of whole grains, leads to the conclusion that the use of the pre-germinated system, in addition to reducing problems with red rice, can also improve the economic gain of the products. DOI:https://doi.org/10.56238/interdiinovationscrese-039